2019
DOI: 10.1542/hpeds.2018-0136
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy for Neonatal Unconjugated Hyperbilirubinemia: Examining Outcomes by Level of Care

Abstract: A B S T R A C TOBJECTIVES: Newborns hospitalized with unconjugated hyperbilirubinemia without critical comorbidities may receive intensive phototherapy (IP) in non-ICU levels of care, such as a mother-newborn unit, or ICU levels of care. Our aim was to compare outcomes between each level. METHODS:Using hospital discharge data from 2005 to 2011 in New York's State Inpatient Database, we performed multivariate analyses to compare outcomes that included total cost of hospitalization, length of stay, 30-day readmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Nine studies [ 3 , 7 , 19 , 23 , 28 , 30 , 32 , 38 , 39 ] identified the primiparous mother as a significant risk factor for readmission for newborns with an odds ratio (OR) ranging from 1.1 to 5.5. Maternal race/ethnicity was cited in eight differing studies [ 7 , 19 , 28 , 30 , 32 , 38 40 ]. Compared with other race/ethnicities, newborns of Asian mothers were more likely to be readmitted following the initial hospitalization at the time of birth (OR = 1.08 to 3.17).…”
Section: Maternal-related Risk Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies [ 3 , 7 , 19 , 23 , 28 , 30 , 32 , 38 , 39 ] identified the primiparous mother as a significant risk factor for readmission for newborns with an odds ratio (OR) ranging from 1.1 to 5.5. Maternal race/ethnicity was cited in eight differing studies [ 7 , 19 , 28 , 30 , 32 , 38 40 ]. Compared with other race/ethnicities, newborns of Asian mothers were more likely to be readmitted following the initial hospitalization at the time of birth (OR = 1.08 to 3.17).…”
Section: Maternal-related Risk Factorsmentioning
confidence: 99%
“…In five studies, health care utilization and family resources, including uninsured health care status, unstable family income and inadequate support for the mother following the discharge, were identified as increasing the risk of newborn readmission [ 3 , 21 , 31 , 39 , 40 ]. Other studies differed, citing mothers who received comprehensive perinatal care as more likely to experience a UHR of their newborn [ 33 , 39 ].…”
Section: Maternal-related Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations